2020
DOI: 10.1021/acs.est.9b06510
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Chromium(III) Immobilization by Organo–Ferrihydrite Co-precipitates: The Significant Roles of Ferrihydrite and Carboxyl

Abstract: The interaction mechanisms of heavy metals with organo−Fe hydroxides co-precipitates (OFC) remain unclear due to the structural complexity of the OFC. In this study, batch experiments were conducted to investigate the immobilization mechanisms of Cr(III) by the OFC, which was prepared by co-precipitating Fe 3+ with rice/rape straw-derived dissolved organic carbon, through sorption and coprecipitation using synchrotron-based X-ray absorption near-edge structure (XANES) spectroscopy and scanning transmission X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(90 citation statements)
references
References 48 publications
(146 reference statements)
5
85
0
Order By: Relevance
“…Anionic functional groups in OM, primarily carboxylates (COO – ), have been reported to have strong affinity for positively charged iron oxide surfaces under acidic pH conditions. A higher adsorption affinity of poly­(acrylic acid) (PAA) to iron oxide than Suwannee River natural OM (SRNOM) was previously reported, due to a higher carboxyl density and linear molecular structure of PAA . The adsorption affinity was also reported to vary for monodentate and polydentate ligands. , Beyond OM adsorption, the formation of insoluble Fe­(III)-organic complex was also reported to result in additional OM sequestration in the coprecipitates. ,,,, For Fe 3+ -OM complexation, carboxyl groups (−COOH) in OM were reported to complex with Fe 3+ ions and thus suppress Fe hydrolysis and precipitation. , Cr 3+ -OM complexation was highly pH dependent, which controlled Cr speciation (e.g., monomeric or polymeric Cr­(III)-OM complexes) in the environment . Regarding Fe/Cr-OM ternary system, only a few studies have investigated Fe/Cr-OM coprecipitation. , Yang et al studied Fe/Cr coprecipitation with dissolved organics derived from rice and rape straws .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anionic functional groups in OM, primarily carboxylates (COO – ), have been reported to have strong affinity for positively charged iron oxide surfaces under acidic pH conditions. A higher adsorption affinity of poly­(acrylic acid) (PAA) to iron oxide than Suwannee River natural OM (SRNOM) was previously reported, due to a higher carboxyl density and linear molecular structure of PAA . The adsorption affinity was also reported to vary for monodentate and polydentate ligands. , Beyond OM adsorption, the formation of insoluble Fe­(III)-organic complex was also reported to result in additional OM sequestration in the coprecipitates. ,,,, For Fe 3+ -OM complexation, carboxyl groups (−COOH) in OM were reported to complex with Fe 3+ ions and thus suppress Fe hydrolysis and precipitation. , Cr 3+ -OM complexation was highly pH dependent, which controlled Cr speciation (e.g., monomeric or polymeric Cr­(III)-OM complexes) in the environment . Regarding Fe/Cr-OM ternary system, only a few studies have investigated Fe/Cr-OM coprecipitation. , Yang et al studied Fe/Cr coprecipitation with dissolved organics derived from rice and rape straws .…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption affinity was also reported to vary for monodentate and polydentate ligands. , Beyond OM adsorption, the formation of insoluble Fe­(III)-organic complex was also reported to result in additional OM sequestration in the coprecipitates. ,,,, For Fe 3+ -OM complexation, carboxyl groups (−COOH) in OM were reported to complex with Fe 3+ ions and thus suppress Fe hydrolysis and precipitation. , Cr 3+ -OM complexation was highly pH dependent, which controlled Cr speciation (e.g., monomeric or polymeric Cr­(III)-OM complexes) in the environment . Regarding Fe/Cr-OM ternary system, only a few studies have investigated Fe/Cr-OM coprecipitation. , Yang et al studied Fe/Cr coprecipitation with dissolved organics derived from rice and rape straws . The dried coprecipitates were characterized by X-ray absorption spectroscopy and scanning transmission X-ray microscopy (STXM) measurements, which revealed the predominance of ferrihydrite-bound Cr­(III) as well as OM-complexed Cr­(III) with carboxyl group as the binding sites .…”
Section: Introductionmentioning
confidence: 99%
“…1 d, arrow d1) after GRSP extraction, indicating the coupling of carbon and iron is disrupted during the extraction of GRSP. The local Fe:C molar ratio affects this organo–ferrihydrite co-precipitates process [ 6 , 7 ]. Therefore, when the local Fe and C+N coupling distribution was lost, some heavy metal(loid)s immobilized via organo-ferrihydrite co-precipitates may be released into the solution.…”
Section: Methods Detailsmentioning
confidence: 99%
“…To better understand and model the OMAs, natural soils are often too complex to be used as model systems for accurate and systematic investigations. Recently, Fe hydroxides have gained increased interest as model adsorbents or co-precipitates for deliberately designed sorption studies that involve important metal species such as Ca or Cr, together with the dissolved organic carbon (DOC) of soils or pure organic acids such as citric acid, [102][103][104][105][106][107][108][109] in order to investigate the interaction/association mechanisms at the molecular level. Among these studies, a novel Fe-Ca-organic carbon ternary system was proposed and confirmed using STXM and other laboratory-based techniques.…”
Section: Biogeochemical Associations Of Other Related Systemsmentioning
confidence: 99%
“…[104][105][106] Recently, we have been investigating organo-Fe hydroxide co-precipitates (OFC) through sorption and co-precipitation batch experiments involving Cr, which were further characterized using STXM. 108,109 The OFC is significantly important in the environment, affecting the immobilization of heavy metals and carbon sequestration. Fig.…”
Section: Biogeochemical Associations Of Other Related Systemsmentioning
confidence: 99%